The adolescent with developmental co-ordination disorder (DCD) - Kirby, Amanda (Jessica Kingsley Publishers, 2004)
Adolescence is hard for most of us, but for an individual with Developmental Co-ordination Disorder (DCD) it can be twice as hard. Amanda Kirby, Medical Director of the Dyscovery Centre and the mother of a DCD child herself, addresses the main difficulties encountered by adolescents with DCD, including building relationships and coping with secondary school. With a common sense approach she provides a series of practical ideas on how individuals can tackle these difficulties making The Adolescent with Developmental Co-ordination Disorder an essential resource for adolescents with DCD, as well.